Improvement of MOSFET matching characterization with calibrated multiplexed test structure. Issue 9 (August 2015) - Welter, L.; Scotto di Quaquero, J.L.; Dreux, P.; Lopez, L.; Aziza, H.; Portal, J.M.
Abstract: This paper presents a way to implement a test structure able to measure accurately a large number of threshold voltage values for Metal Oxide Semiconductor Field Effect Transistors (MOSFETs) matching characterization. A multiplexed system able to select a single transistor among others in a small array is used. This architecture guarantees a similar environment for all transistors in the array, while requiring a small number of pads for measurement. Moreover, the influence of the multiplexer switches can be evaluated: their unwanted contribution to the measurement can therefore be compensated. An experimental study to evaluate the influence of this multiplexer on measurement and the efficiency of the compensation is conducted. Silicon results are presented in order to validate the concept. Highlights: A test structure for transistor matching evaluation is presented. This production-ready structure is small enough to fit into wafers scribe lines. A large number of transistors can be accurately measured with one structure. This can be achieved thanks to calibrated multiplexers. The concept has been validated with Monte-Carlo simulations and silicon results.